2013
DOI: 10.1080/00223891.2012.740540
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrics and Validity of the Dutch Experiences in Close Relationships–Revised (ECR–r) in an Outpatient Mental Health Sample

Abstract: The Experiences in Close Relationships-Revised (ECR-r) is a self-report instrument to assess adult attachment style that seems to have appropriate psychometric qualities. The ECR-r has been most widely studied in student and community samples. In this study we report factor structure, reliability, and construct validity of the Dutch translation of the ECR-r in an outpatient mental health sample (N = 262). The original factor structure could satisfactorily be replicated, the reliability of the ECR-r was also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
3
32
2
8
Order By: Relevance
“…Analyzing these results in more detail, one can observe that some studies tend to report mostly significant results, while other studies report varying p-values. For example, Pearson et al [41] show exclusively significant correlation coefficients and Kooiman et al [42] report similar results. In contrast, results of the studies of Chen and Mallinckrodt [26] and Lawson and Brossart [43] range from not significant to highly significant.…”
Section: Adult Attachment and Specific Interpersonal Octantssupporting
confidence: 59%
“…Analyzing these results in more detail, one can observe that some studies tend to report mostly significant results, while other studies report varying p-values. For example, Pearson et al [41] show exclusively significant correlation coefficients and Kooiman et al [42] report similar results. In contrast, results of the studies of Chen and Mallinckrodt [26] and Lawson and Brossart [43] range from not significant to highly significant.…”
Section: Adult Attachment and Specific Interpersonal Octantssupporting
confidence: 59%
“…A Dutch version of the ECR-R demonstrated good reliability for attachment avoidance ( = .94) and attachment anxiety ( = .92). Moreover, confirmatory factor analysis showed that the hypothesized two-factor model of the ECR-R, showed a good fit with the data, χ2(53, n = 262) = 169.650, CFI = .95, RMSEA = .092 (Kooiman, Klaassens, van Heloma Lugt & Kamperman, 2013). Internal consistency reliability was also good in our sample for attachment anxiety (λ-2 = .90;  = .90) and avoidance (λ-2 = .86;  = .85).…”
Section: Attachment Dimensionsmentioning
confidence: 92%
“…Research on the psychometric properties of the ECR has revealed problems regarding the precise measurement in particular the ‘secure’ end of each attachment dimension [ 8 ; 9 ; 10 ]. One of these problems pertains to the scoring of the scales.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the psychometric properties of the ECR-R have been tested in nine studies [ 8 ; 10 ; 13 ; 14 ; 15 ; 16 ; 17 ; 18 ; 19 ]. The studies highlight three limitations that have, however, yet to be overcome.…”
Section: Introductionmentioning
confidence: 99%